Green Fluorescent Protein- and Discosoma sp. Red Fluorescent Protein-Tagged Organelle Marker Lines for Protein Subcellular Localization in Rice - Chen, Ziqiang; Zheng, Wenhui; Chen, Longhai; Li, Chenlu; Liang, Tingmin; Chen, Zaijie; Xu, Huibing; Han, Yijuan; Kong, Lan; Zhao, Xu; Wang, Feng; Wang, Zonghua; et al. (Frontiers in Plant Science, 2019)
The subcellular localization of proteins is a fundamental aspect of protein functions. Determining the subcellular localization is important for understanding the biological functions of proteins. Here, we developed a set of rice organelle marker lines, in which the expressing fluorescent organelle markers could be used as comparative standards in determining the subcellular localization of the protein of interest. We constructed GFP- and/or DsRed-tagged organelle markers targeted to the endoplasmic reticulum (ER), mitochondria, Golgi apparatus, peroxisome, actin cytoskeleton, plastid, tonoplast, plasma membrane, and nucleus, respectively. The utility of the rice marker lines for protein subcellular localization studies was demonstrated by detecting a nucleus-localized OsWRKY45 and a mitochondria-associated NbHxk1 in protoplasts of the GFP-H2B and the AtWAK2-GFP-HDEL lines, respectively. Using a sheath-inoculation method, followed by a live-cell imaging, we detected co-localization of a Magnaporthe oryzae PWL2:mCherry:NLS fusion with the nucleus marker in the GFP-H2B rice epidermal cells, confirming the translocation of the M. oryzae effector PWL2 into host cells, and further demonstrating the feasibility of using the organelle marker lines for studying dynamics of proteins in rice cells in the interactions between rice and pathogens. The set of organelle marker lines developed in the present study, provides a valuable resource for protein subcellular localization studies in rice.